O movimento de concentração e centralização de capital no capitalismo contemporâneo: aspectos da dinâmica de fusões & aquisições sob a dominância financeira - Gomes, Carlos Campos (2021)
The aim of the work is to analyze the movement of concentration and centralization of capital in the dynamics of contemporary capitalism in crisis and how substantial changes have occurred in the determinants of mergers and acquisitions when understood in the light of a broad process of “financialization”. The broad concept of concentration and centralization is understood as arising from the “laws of movement” and the logic that is imposed on Capital in its destiny of valorization. François Chesnais' contribution is highlighted by the centrality attributed to “interestbearing capital” and “fictitious capital” as the main actors of a new form of accumulation derived from a broad process of centralization. Following its historical development, we highlight the emergence of joint-stock companies as the great “invention” of Capital that will make it possible to overcome the first restrictions imposed on its expansion. A growing component of fictitious capital comes to increasingly influence mergers and acquisitions, causing a displacement of its gravitational axis from the orbit of the strict determinants of competition in order to overcome the limits imposed on its expansion. This analysis culminates in the observation that if in the past these operations were directed towards the conquest of greater market power and the presence of fictitious capital was only an associated and necessary component for the realization of these operations, with the rise of abstract wealth (capital fictitious ) this mechanism is no longer an auxiliary to become an objective in itself. Market power translates into greater capacity to create fictitious capital, and both are reinforced. To deeping the discussion, we direct our efforts to present an overview of the concentration and centralization of capital through a structured method of searching in the main international Marxist periodicals. The convergences and divergences between reasons and interpretations are taken and incorporated to form a broad framework from which we extract the core of the debate that points to the successive crises of capitalism and its contradictory nature. Finally, we try to concatenate the multiple approaches to demonstrate the nature of the changes that have taken place and the meaning attributed to mergers and acquisitions “under financial dominance”